THE ROLE OF INNOVATION IN THE DEVELOPMENT OF THE COUNTRY’S ECONOMY: ANALYSIS AND RESULTS - Ikram Abdullayevich Navruzov (Modern American Journals, 2025)
In this article, scientific-theoretical views on the financing of innovation activities, theoretical aspects of innovation implementation. Also, the analysis of the sources of financing innovative projects, the experiences of foreign countries in financing innovative activities were studied, and theoretical conclusions and practical recommendations were formed on the prospects of transitioning to the innovative economy through the acceleration of innovative activities.
Keywords: Innovation market, scientific research developments, technologies, sources of financing, innovative position, innovative economy.